2021
DOI: 10.1037/pap0000337
|View full text |Cite
|
Sign up to set email alerts
|

Eating pathology and Psychodynamic Diagnostic Manual (PDM-2) diagnostic assessment: Implications for treatment outcomes in a psychodynamic-oriented residential setting.

Abstract: The Diagnostic and Statistical Manual of Mental Disorders (DSM-5) categorical classification of eating disorders (ED) has faced substantial criticism due to its limited ability to assess patients’ individual characteristics and thereby evaluate the most appropriate treatment options. The current study aimed at exploring the validity of the Psychodynamic Diagnostic Manual (PDM-2) diagnostic approach to ED by evaluating the treatment outcomes of a psychodynamic-oriented residential intervention. At the start of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Thus, the S Axis provides only one of three crucial perspectives and assists clinicians in creating a multifaceted diagnostic profile of the patient, to determine the best treatment options [41]. With respect to personality features in EDs, the manual highlights the relevance of three empirically-based personality configurations that broadly correspond to: (a) an underregulated subtype, characterized by patterns of impulsive behavior and affective lability/instability, borderline and bulimic features, and feelings of emptiness and emotional hunger [42]; (b) an overregulated subtype, characterized by inhibition and a restricted behavioral/affective presentation; schizoid, avoidant, and obsessive-compulsive features; and anorexic symptoms [43]; and (c) a high-functioning/perfectionistic subtype, characterized by normative levels of personality functioning and less severe ED psychopathology [44]. These personality profiles have been confirmed by a substantial body of research using different assessment tools with both single diagnostic and mixed ED samples [45][46][47][48][49].…”
Section: Beyond Symptoms: the Psychodynamic Diagnostic Manual (Pdm-2)...mentioning
confidence: 99%
“…Thus, the S Axis provides only one of three crucial perspectives and assists clinicians in creating a multifaceted diagnostic profile of the patient, to determine the best treatment options [41]. With respect to personality features in EDs, the manual highlights the relevance of three empirically-based personality configurations that broadly correspond to: (a) an underregulated subtype, characterized by patterns of impulsive behavior and affective lability/instability, borderline and bulimic features, and feelings of emptiness and emotional hunger [42]; (b) an overregulated subtype, characterized by inhibition and a restricted behavioral/affective presentation; schizoid, avoidant, and obsessive-compulsive features; and anorexic symptoms [43]; and (c) a high-functioning/perfectionistic subtype, characterized by normative levels of personality functioning and less severe ED psychopathology [44]. These personality profiles have been confirmed by a substantial body of research using different assessment tools with both single diagnostic and mixed ED samples [45][46][47][48][49].…”
Section: Beyond Symptoms: the Psychodynamic Diagnostic Manual (Pdm-2)...mentioning
confidence: 99%
“…The average length of clinical psychotherapy practice was 10.1 years (SD = 3.07; range = 7-15) and the average time spent per week practicing psychotherapy was 22.7 h (SD = 5.14; range = 15-35). All of the present study data were added to those of the patients and clinicians who participated in previous investigations using the same assessment tools (Muzi et al, 2020(Muzi et al, , 2021.…”
Section: Participantsmentioning
confidence: 99%
“…Although research on personality as a predictor of ED outcome is sparse, some relevant studies, drawing on the pathoplasty model, have found that PDs are commonly associated with poorer response to treatment (Steinhausen, 2002(Steinhausen, , 2009Thompson-Brenner and Westen, 2005;Wildes et al, 2011;Muzi et al, 2020Muzi et al, , 2021. Further research has suggested that high attrition, low compliance, dropout, symptom chronicity, low recovery rates, and low efficacy of therapeutic interventions relate to the personality characteristics of individual patients (Pham-Scottez et al, 2012;Martinez and Craighead, 2015;Levallius et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings also point to a reduced capacity to mentalize ( 16 19 ), which is supported by clinical contributions and qualitative empirical work ( 20 , 21 ). Additionally, in one study, a relationship between a higher capacity to mentalize and better outcomes was found ( 22 ). Difficulties in self-related information processing and perspective taking were also supported by findings from neuroimaging studies [see e.g., ( 23 )].…”
Section: Introductionmentioning
confidence: 99%